PENGARUH BIMBINGAN BELAJAR TERHADAP HASIL USBN MATA PELAJARAN EKONOMI SISWA SMA NEGERI 2 PONTIANAK - Ramadhan, Muhammad Syahri; Aminuyati, Aminuyati; Asriyati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of tutoring on National Standard School Examination (USBN) Results of Economic Subjects of XII IPS students of SMA Negeri 2 Pontianak. The research method used associative with the EXPO Facto research form. Respondents of this study were all students of class XII IPS SMA Negeri 2 Pontianak. The population in this study was 190 students, with a total sample of 66 students. The sampling technique in this study uses probability sampling techniques. For data collection using 1) indirect communication techniques, 2) documentary study techniques. The results of this study indicate that 1) the implementation of tutoring for XII IPS students of SMA Negeri 2 Pontianak has an average real score of 5143 with a percentage of 77.92% in the high category, 2) the results of USBN in economic subjects have an average score of 72.83 % with good category, 3) there is the influence of tutoring on National Standard School Examination (USBN) Results of economic subjects of class XII IPS students of SMA Negeri 2 Pontianak which is shown in the significance of the count of 0.005 <? 0.000. The magnitude of the coefficient of determination in this study amounted to 45.9% while the remaining 54.1% was influenced by the independent variables not examined in this study. Keywords: Tutoring, National Standard School Exam Results (USBN), Economic Subjects